2009
DOI: 10.1007/s00018-009-0191-3
|View full text |Cite
|
Sign up to set email alerts
|

ADP receptor P2Y13 induce apoptosis in pancreatic β-cells

Abstract: Pancreatic beta-cell loss represents a key factor in the pathogenesis of diabetes. Since the influence of purinergic signaling in beta-cell apoptosis has not been much investigated, we examined the role of the ADP receptor P2Y(13) using the pancreatic insulinoma-cell line MIN6c4 as a model system. Real time-PCR revealed high expression of the ADP receptors P2Y(1) and P2Y(13). Adding the ADP analogue, 2MeSADP, to MIN6c4 cells induced calcium influx/mobilization and inhibition of cAMP production by activation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 31 publications
1
33
0
Order By: Relevance
“…In a previous study, we showed that stimulation of purinergic P2Y 13 receptors on beta cells activates apoptotic pathways [6]. The aim of the present study was to determine if high glucose and free fatty acids contribute to beta cell apoptosis via autocrine/paracrine activation of the P2Y 13 receptor.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a previous study, we showed that stimulation of purinergic P2Y 13 receptors on beta cells activates apoptotic pathways [6]. The aim of the present study was to determine if high glucose and free fatty acids contribute to beta cell apoptosis via autocrine/paracrine activation of the P2Y 13 receptor.…”
Section: Discussionmentioning
confidence: 98%
“…High glucose and palmitate stimulation of MIN6c4 cells causes autocrine activation of Caspase-3 through P2Y 13 We have previously reported that activation of the purinergic receptor P2Y 13 , on MIN6c4 cells, results in activation of proapoptotic pathways [6]. We next investigated if high glucose or palmitate could influence Caspase-3 level in MIN6c4 insulinoma cells cultured for 36 h and to what extent this effect could be inhibited by MRS2211.…”
Section: Atp Release Triggered By High Glucose or Palmitate Inhibits mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that P2Y 6 receptor agonists not only increase insulin secretion, but prevent b-cell death induced by tumour necrosis factor-a (Balasubramanian et al 2010). On the other hand, it seems that activation of the P2Y 13 receptor of the mouse pancreatic insulinoma cell line, MIN6C4, has a pronounced proapoptotic effect; 2-metylthio ADP reduced cell proliferation and increased caspase-3 activity, effects that were reversed by the P2Y 13 receptor antagonist, MRS2211 (Tan et al 2010). Extracellular ATP (1 mM) increased insulin secretion in mouse b-cell lines, probably via P2Y 1 and P2X 4 receptors, though at higher ATP concentrations in the medium, cell viability decreased (Ohtani et al 2011).…”
Section: Diabetes and Pancreasmentioning
confidence: 99%
“…(23) In addition, it was recently shown that blocking the P2Y 13 receptor can mediate ERK1/2 involvement in b-cell apoptosis. (24) Interestingly, ERK1/2 signaling was demonstrated to be involved in osteoblastic response upon mechanical strain and fluid flow. (17,25) Given the expression of P2Y 13 receptor by osteoblasts and the observed negative feedback pathway for ATP release in red blood cells, we hypothesized that the P2Y 13 receptor would play a role in the osteogenic response to mechanical stimulation via regulating ATP metabolism in osteoblasts.…”
mentioning
confidence: 99%